Laser augmented by brachytherapy versus laser alone in the palliation of adenocarcinoma of the oesophagus and cardia: a randomised study. Issue 2 (1st February 2002) - Spencer, G M; Thorpe, S M; Blackman, G M; Solano, J; Tobias, J S; Lovat, L B; Bown, S G
Abstract : Background: Many patients with advanced malignant dysphagia are not suitable for definitive treatment. The best option for palliation of dysphagia varies between patients. This paper looks at a simple technique for enhancing laser recanalisation. Aim: To assess the value of adjunctive brachytherapy in prolonging palliation of malignant dysphagia by endoscopic laser therapy. Patients: Twenty two patients with advanced malignant dysphagia due to adenocarcinoma of the oesophagus or gastric cardia, unsuitable for surgery or radical chemoradiotherapy. Methods: Patients able to eat a soft diet after laser recanalisation were randomised to no further therapy or a single treatment with brachytherapy (10 Gy). Results were judged on the quality and duration of dysphagia palliation, need for subsequent intervention, complications, and survival. Results: The median dysphagia score for all patients two weeks after initial treatment was 1 (some solids). The median dysphagia palliated interval from the end of initial treatment to recurrent dysphagia or death increased from five weeks (control group) to 19 weeks (brachytherapy group). Three patients had some odynophagia for up to six weeks after brachytherapy. There was no other treatment related morbidity or mortality. Further intervention was required in 10 of 11 control patients (median five further procedures) compared with 7/11 brachytherapy patients (median two further procedures). There was no difference in survival (median 20 weeks (control), 26 weeks (brachytherapy)). Conclusions: Laser therapy followed by brachytherapy is a safe, straightforward, and effective option for palliating advanced malignant dysphagia, which is complementary to stent insertion.